Discovery of three strongly lensed quasars in the Sloan Digital Sky Survey. (14th March 2018) - Williams, P R; Agnello, A; Treu, T; Abramson, L E; Anguita, T; Apostolovski, Y; Chen, G C-F; Fassnacht, C D; Hsueh, J W; Lemaux, B C; Motta, V; Oldham, L; et al.
Abstract: We present the discovery of three quasar lenses in the Sloan Digital Sky Survey, selected using two novel photometry-based selection techniques. The J0941+0518 system, with two point sources separated by 5.46 arcsec on either side of a galaxy, has source and lens redshifts 1.54 and 0.343. Images of J2257+2349 show two point sources separated by 1.67 arcsec on either side of an E/S0 galaxy. The extracted spectra show two images of the same quasar at z s = 2.10. SDSS J1640+1045 has two quasar spectra at z s = 1.70 and fits to the SDSS and Pan-STARRS images confirm the presence of a galaxy between the two point sources. We observed 56 photometrically selected lens candidates in this follow-up campaign, confirming three new lenses, re-discovering one known lens, and ruling out 36 candidates, with 16 still inconclusive. This initial campaign demonstrates the power of purely photometric selection techniques in finding lensed quasars.